WearDrive: Fast and Energy-Efficient Storage for Wearables - Huang, Jian; Badam, Anirudh; Chandra, Ranveer; Nightingale, Edmund B (Annual Technical Conference (ATC'15), 2015)
Size and weight constraints on wearables limit their battery capacity and restrict them from providing rich functionality. The need for durable and secure storage for personal data further compounds this problem as these features incur energy-intensive operations. This paper presents WearDrive, a fast storage system for wearables based on battery-backed RAM and an efficient means to offload energy intensive tasks to the phone. WearDrive leverages low-power network connectivity available on wearables to trade the phone’s battery for the wearable’s by performing large and energy-intensive tasks on the phone while performing small and energy-efficient tasks locally using battery-backed RAM. WearDrive improves the performance of wearable applications by up to 8.85x and improves battery life up to 3.69x with negligible impact to the phone’s battery life.